TEACHER PROFESSIONAL TRAINING: PROFILE AND UNDERSTANDING OF TEACHERS OF A PUBLIC SCHOOL OF RS - Soares, Renata Godinho; Copetti, Jaqueline (Práxis Educacional, 2020)
The main objective of this study was to identify the profile and understanding of teachers about teacher vocational training and its importance for teaching practice. The study included 21 teachers from the final years of elementary school of a municipal school, who answered a questionnaire with closed questions to profile teachers and open questions to identify the understanding of training education and the importance of this issue. Regarding the teaching profile, most of them are women, the average time of training was 14 years, with an average time of work as a teacher of 13 years. Related to the understanding of Teacher Professional Training, the teachers expanded this, considering it not only as aspects for career progression, but also the reflection on their action in practice in the classroom. Participants consider it extremely relevant to stay up-to-date and in constant professional training. It is considered important studies that identify the needs and importance of formative actions that teachers seek, in order to offer significant courses consistent with the school reality where these professionals are.